Profile of human anti-rabies care and post-exposure prophylaxis in the state of São Paulo - da Costa Andrade, Bruno Fonseca Martins [UNESP] (2023)
Background: Rabies is an anthropozoonosis that greatly impacts public health and is transmitted by infected mammals. Aggression by animals is notifiable and may result in anti-rabies post-exposure prophylaxis (PEP). This study aimed to characterize anti-rabies PEP notifications in São Paulo state, Brazil. Methods: A descriptive study was conducted using data provided by the SINAN between 2013 and 2017. Results: A total of 572,889 aggressions were recorded during the study period, characterized mostly by dogs (83.5%), single wounds (56.9%), superficial wounds (58.6%), and hands/feet (34.6%). Conclusions: Animal observation was the most frequent recommendation, even in cases of attacks from non-domestic animals.